Future projections of seasonal patterns in temperature-related deaths for Manhattan - Li, Tiantian (2013)
Global average temperatures have been rising for the past half-century, and the warming trend has accelerated in recent decades(1). Further warming is expected over the next few decades, with significant regional variations. These warming trends will likely result in more frequent, intense and persistent periods of hot temperatures in summer, and generally higher temperatures in winter. Daily death counts in cities increase markedly when temperatures reach levels that are very high relative to what is normal in a given location(2–4). Relatively cold temperatures also appear to carry risk(2,4). Rising temperatures may result in more heat-related mortality but may also reduce cold-related mortality, and the net impact on annual mortality remains uncertain. Here we use 16 downscaled global climate models and two emissions scenarios to estimate current and future seasonal patterns in temperature-related mortality in Manhattan, New York. All 32 projections yielded warm season increases and cold season decreases in temperature-related mortality, with positive net annual temperature-related deaths in all cases. Monthly analyses showed that the largest percentage increases may occur in May and September. These results suggest that, over a range of models and scenarios of future greenhouse gas emissions, increases in heat-related mortality could outweigh reductions in cold-related mortality, with shifting seasonal patterns.